A Comparative Study on the Execution Time of Inheritance Distribution from the Perspectives of Islamic Law and Civil Law - Winni Angelia Eka Putri; Mairul Mairul (Fox Justi : Jurnal Ilmu Hukum, 2026)
Inheritance is a crucial aspect of family law, yet the prevalent socio-cultural practice of "living inheritance" (warisan hidup) in Indonesia often creates conceptual and juridical confusion between grants (hibah) and actual inheritance. This research aims to comparatively analyze the precise execution time of inheritance distribution according to normative Islamic Law and the Indonesian Civil Code (KUHPerdata) to resolve these socio-legal tensions. Employing a normative legal research method with a qualitative comparative approach, this study exclusively analyzes primary and secondary legal materials, including the Qur'an, the Compilation of Islamic Law (KHI), and the KUHPerdata. The findings reveal that neither legal system explicitly sets a rigid deadline or expiration period for distribution post-mortem. However, Islamic Law mandates a strictly sequential, ijbārī (compulsory) process requiring the prior settlement of funeral costs, debts, and testamentary wills before asset division. Conversely, the KUHPerdata provides a highly flexible, consent-driven mechanism that depends entirely on the heirs' free will and proactive demands. This study concludes that while Civil Law permits procedural delays, unnecessary postponement is strongly discouraged across both systems to prevent overlapping claims. Understanding these temporal boundaries is vital for society to ensure absolute legal certainty, utilize appropriate lifetime legal instruments accurately, and maintain long-term familial harmony.